KONSTRUKSI FILSAFAT AKUNTANSI, DAN AUDITING STUDI ETNOGRAFI, DAN HERMENEUTIKA PADA CANDI PRAMBANAN JOGJAKARTA - Apollo Apollo (JURNAL MANAJEMEN PENDIDIKAN DAN ILMU SOSIAL, 2020)
The research resulted in the Reconstruction of Accounting Philosophy, and Auditing, Dialectical Approach, especially based on the Logic, Hermeneutic, Semiotic, and Rhetorical approaches. The originality of this research is the innovative philosophy of science in Indonesia. This research is expected to be the basis for the development of thinking through research on Ethnographic and Hermeneutic Studies at Prambanan Temple, Jogjakarta. Transubstantial Hermeneutics and semotics in Trimurti: Sang Hyang Wenang (Brahma), Sang Hyang Wening (Wisnu), Sang Hyang Guriang Tunggal (Siwa). In the third hermeneutic meaning (Trimurti) or Symbol, the ontological meaning is shifted or interpreted hermeneutically to become "The Prambanan Text Book" resulting in three modes of "Being" in humans, namely being in himself, being for himself, and being for others. The Prambanan Textbook or “The Prambanan Textbook” is a method of Hegel's dialectical system consisting of three stages. The first is that the thesis is represented by Sang Hyang Wenang (Brahma), which is to construct a certain doctrine of statements. The second is the antithesis (Sang Hyang Guriang Tunggal (Siwa), which is an argumentative statement that rejects the thesis. The third is synthesis (Sang Hyang Wening (Wisnu), which is an attempt to reconcile the tension between the thesis and the antithesis. Then the text "The Prambanan Text Book" is represented by Sang Hyang Guriang Tunggal (Siwa) is to build a framework of "consciousness (thinking), and material dialectics" using themes in the approaches of Paradox (Antithesis), Anomaly, Antinomy, Alienation, Anomie, and Contradiction. The Trans Substance using hermeneutics Schleiermacher 1768-1834), Dilthey (1833-1911), Heidegger (1889-1976), Ricoeur (1913-2005), Derrida (1930-2004), Gadamer (1900-2002), Bultmann (1884- 1976), Habermas, to explain the Prambanan Myth into Episteme, and Idiology. To support the trans substance of the meaning of Prambanan Temple, a method of understanding is used with cognitive semiotics, Pierce (1839-1914), Saussure (1857-1913), Barthes, Ogden, Richards (1949). The results of research on the Philosophy of Accounting and Auditing (Ethnographic Study of Hermeneutic Reinterpretation Prambanan Temple, Jogjakarta) "are as follows: Accounting is a dialectic of writing behavior conveyed to readers, after reviewing: Criticism 1, and Criticism 2,3. In accordance with the rules of writing, and the rules are made to protect users or stakeholders. Accounting Science as a function of producers to consumers in the form of text financial statements that are reliable and relevant. The Prambanan theme in the Auditing context is that the dialectical method has elements of Paradox (Antithesis) and Contradiction, as its virtues. The relationship between accounting and auditing is the building of a shared awareness (thinking) framework after public testing using the Paradox (Antithesis) approach. Contradiction is carried out through critical thinking & critical reading. Relational Dialectics states that connected life is characterized by continuous tensions between contradictory impulses. Paradox (Antithesis), contradiction in the field of economics-accounting is a formation of the capitalist system, with the instrumental ratio of material dialectics as the main driving force for human "alienation". The meaning of work is alienation itself. The episteme and truth of accounting and auditing are only "Perspectivism" as a need to interpret the world and its relations. So through dialectics is a way to harmonize "Perspectivism" trapped in "space and time. And the truth of "Perspectivism" is in time.